Prevalence of Essential Hypertension and Assessment of Cardiovascular Risk of Pakistani Adults in Outpatient Setting - M A Ebrahim ,Zeeshan Hassan (Journal of Rawalpindi Medical College, 2018)
Background: To assess the prevalence of essential hypertension and evaluate cardiovascular risk in patients in Pakistan. Methods:This cross-sectional, non-interventional study was conducted at multiple centres throughout Pakistan. Data was collected from patients of either gender, ≥18 years of age, seeking routine medical consultation. Diagnosis and staging of hypertension was carried out using guidelines laid by Seventh Report of Joint National Committee (JNC 7). Genderwise Framingham scores were calculated based on non-laboratory and laboratory parameters. Results: Out of 2336 patients evaluated, prevalence of hypertension and prehypertension was 51.5% and 31.4% , respectively. A total of 501 patients had coprevalent diabetes and hypertension. Ten-year Framingham scores calculated using non-laboratory parameters showed 56% (947/1693) patients aged ≥30 years were at medium-to-high risk for cardiovascular disease (CVD). While Framingham scores based on laboratory or non-laboratory parameters were not significantly different for men, in women the nonlaboratory based score was higher. Angiotensinconverting enzyme inhibitors and calcium channel blockers were antihypertensive agents of choice. Conclusions: Since prevalence of prehypertension and hypertension in Pakistani adults continues to be on rise and substantial proportion of study population is at medium-to-high risk of developing CVD within the next 10 years, regular BP monitoring and risk scoring is mandated for identification of at-risk population and optimal management of CVD.